Wolfgang Weiss, Pandemic and Administrative EU Soft Law: Persistent Challenges to the Rule of Law in the EU and Possible Solutions, „Review of European Administrative Law” 2022, vol. 15, no. 1, pp. 7-28, https://doi.org/10.7590/187479822X16484711705972 - Narożniak, Agnieszka (Studia Prawa Publicznego, 2022)
Wolfgang Weiss, Pandemic and Administrative EU Soft Law: Persistent Challenges to the Rule of Law in the EU and Possible Solutions (Pandemiczne i administracyjne unijne prawo miękkie: trwałe wyzwania dla rządów prawa w UE i możliwe rozwiązania), „Review of European Administrative Law” 2022, vol. 15, no. 1, pp. 7-28, https://doi.org/10.7590/187479822X16484711705972